PENINGKATAN KINERJA CAMPURAN BERASPAL DENGAN KARET ALAM DAN KARET SINTETIS. - Tjitjik Wasiah Suroso (Direktorat Bina Teknik Jalan dan Jembatan, 2007)
One of the efforts in improving asphalt quality is intended to prevent deformation on pavement by adding rubber to asphalt. There are two types of rubber i.e. natural and synthetic rubbers. Natural rubber mostly can be found in rubber plantation in Indonesia. Therefore, the effective use of either natural or synthetic rubber can reduce the impact of heavy traffic load on road pavements which is currently occurred in some parts of Indonesia. Natural rubber has commonly been used, however, it is an organic substance that easily oxidized and polymerized by ultraviolet resulting in the reduction of its elasticity. On the other hand, synthetic rubber is less susceptible against oxidation and temperature. This paper describes a research result regarding the influence of addition a natural and synthetic rubber on asphalt quality and the performance of asphalt mix using Marshall test, Modulus resilient using UMATTA, dynamic stability and rate of deformation using Wheel Tracking Machine. The result showed that the addition of synthetic rubber to asphalt resulted in a better properties compared to the addition of natural asphalt especially in its resistance to aging, softening point, dynamic stability and rate of deformation. Keywords : Asphalt, Natural and synthetic rubber, Dynamic stability, Rate of deformation, Resilient modulus